Urgensi Dan Dampak Pemberlakuan Ambang Batas 30% Perempuan Dalam Partai Politik Untuk Calon Anggota Legislatif - Riska Buhungo; Erman I. Rahim; Abdul Hamid Tome (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research examines the pattern of recruitment of women in political parties to meet the threshold of 30% of Legislative Members in Indonesia, starting from regulations governing the rights and obligations of political parties as regulated in law, and specifications related to the recruitment process from political parties contained in in the AD/ART of political parties. This research is classified as normative empirical research with a statutory approach and a case approach. Research material was collected through interviews and document studies and then analyzed from a perspective. The results of the research show that the recruitment process for each political party is different and by stating the party's interests, there is no reference process regulated in statutory regulations. The researcher provides recommendations in this research related to the formation of statutory regulations for the recruitment process so that they become a reference for each party. politics, as well as providing political education to women in stages as well as evaluations that become material for party development.